A Midsummer Night's Dream - Edited By Turner, W (New Delhi OS. Chand & Company Ltd, 1997)
Shakespeare's play about devilish fairies, bedeviled lovers and tradesmen-actors. Plots intertwine as entangled love affairs, the comical performance of a "play within a play" by the tradesmen of Athens, and the antics in fairyland among King Oberon and his queen Titania produce a bizarre series of entanglements, but all ends happily.
Include Illustrations.
Keywords: Shakespeare, William, 1564-1616 -- Greece--Athens